Private Health Sector Assessment in Tanzania - White, James (World Bank, 2015)
Mainland Tanzania exemplifies the developing world’s struggle to achieve middle-income status while confronting widespread poverty and substantial health challenges. Tanzania’s struggle with HIV/AIDS, reproductive and child health, malaria, and tuberculosis are characterized by both positive recent trends and persistent challenges. A high disease burden coupled with finite public sector resources has led the government of Tanzania to increasingly seek innovative tools to protect the health and wellbeing of its citizens. Previous reform efforts have included decentralizing decision making authority to local governments to improve the responsiveness of public sector programs and partnering with faith-based health facilities to expand the government’s reach into rural areas. In recent years, the government has increasingly tried to leverage the private health sector’s capacity to strengthen the Tanzanian health system- first by removing the ban on private practice in 1991 and then by emphasizing PPPs in its national health policies and strategic plans. In response, the private health sector has grown and organized into several umbrella organizations, such as the Christian Social Services Commission (CSSC), the Association of Private Health Facilities in Tanzania (APHFTA), and the National Muslim Council of Tanzania (BAKWATA). Together, the public and private sectors have laid the policy groundwork for improved collaboration. Engaging the private sector beyond dialogue and operationalizing PPPs has proven more difficult due to lingering distrust and a lack of communication between the sectors at lower levels.